O impacto das Relações Públicas digitais e do marketing digital: análise das estratégias encontradas no perfil do Arma Eu Taubaté no Instagram - Castello, Thamara de Oliveira Pires (Brasil, 2025)
Innovation has enabled a technological evolution that has been changing the way we live and especially how society communicates. Due to the increasingly rapid emergence of multiple information and communication technologies, it is necessary for companies to learn to communicate in an increasingly direct, interactive, and intimate manner with their audiences. For the dynamic effectiveness of these new forms of communication, public relations professionals must reflect on the use of these new technologies, seeking to understand in a deeper and more systematic way how the use of these tools can collaborate to promote their own interests. Knowing more about technology brings extra power to position oneself strategically. Instagram presents an important space for these professionals to operate; however, mastering this digital tool is fundamental to amplify the activities in the field. Seeking to present marks of its existence and utilization, the research aims to demonstrate how Digital Public Relations develop in the promotion of companies in the social media environment. Therefore, a case study of the Arma Eu Taubaté profile on Instagram will be conducted. The research's main methodology is basic exploratory research with a qualitative approach, using bibliographic research and case studies, as well as content analysis. The aim is to observe which Digital Public Relations and Digital Marketing strategies the profile employs and what the possible impacts on the organizational image of the involved brands are.